First study on oxyuriosis in horses from Algeria: Prevalence and clinical aspects - KOUIDRI, M; BOUMEZRAG, A; SELLES SIDI MOHMMED, A; TOUIHRI, Z; SASSI, A; CHIBI, AS (Journal of the Hellenic Veterinary Medical Society, 2021)
The present study was carried out the Tiaret region, on horses belonging to the Chaouchaoua National Haras, ONDEEC and on two private farms during the period from February 05th to April 17th, 2019. It aims to assess the overall prevalence of equine oxyuriosis in the area and to describe the most dominant clinical signs of this parasite infection. Scotch tape test was applied on 176 horses randomly selected and the microscopic observation of slides was carried out at the parasitology laboratory of the Veterinary institute of Tiaret. The overall prevalence of Oxyuris equi was 38.64% with females being more infected (37.04%) than males (20.45%). The prevalence of oxyuriosis was higher in fillies (70%) than in foals (48.39%).The high prevalence of Oxyuris equi was recorded in the private farms with a percentage of 85% and 44% in farm 1 and 2, respectively. The more commonly clinical signs were tail rubbing in 42% and scratching in 32% of positive horses.Equine oxyuriosis is a common infection in the study area and requires the application of hygienic measures with more therapeutic and preventive care.